Analisis kemampuan pemecahan masalah matematis siswa dalam menyelesaikan soal statistika berdasarkan level kemampuan siswa SMP kelas VIII - Friska Rustella; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
The lack of students' mathematical problem solving abilities causes difficulties in solving problems, especially with statistical data. The research objective is to describe students' abilities in solving mathematical problems related to statistics. Qualitative methods are used as research methods. Participants who were taken as research subjects consisted of 80 class VIII students of SMPN 1 Parongpong. Subjects were divided into three groups, namely students with high abilities (10), students with moderate abilities (45), and students with low abilities (25). Data collection techniques used test questions in the form of student math problem solving tests and questions in the form of essay tests. The results showed that overall the students' mathematical problem solving abilities were in the high category, totaling 8 people with a percentage of 10% with a criterion score of less than 79.43. The ability to solve mathematical problems in the moderate category is 42 students with a percentage of 52.5% and an initial score of 36.56 to less than 79.43. On the other hand, there are 30 students in the low category with math problem solving abilities which have a percentage of 37.5%, and an initial score of less than 36.5.